104k views
1 vote
If f and t are both even functions, is f 1 t even? If f and t are both odd functions, is f 1 t odd? What if f is even and t is odd? Justify your answers.

1 Answer

4 votes

If the
f(x) and
t(x) are even function then
fo\ t\ (x) is an even function, if
f(x) and
t(x) are odd function then the function
fo\ t\ (x) is an odd function and if
f(x) is even and
t(x) is odd then the function
fo\ t\ (x) is an even function.

Further explanation:

An even functrion satisfies the property as shown below:


\boxed{f(-x)=f(x)}

An odd functrion satisfies the property as shown below:


\boxed{f(-x)=-f(x)}

Consider the given composite function as follows:


\boxed{fo\ t\ (x)=f\left(t(x))\right}

If both the function
f(x) and
t(x) are even function.


\begin{aligned}fo\ t\ (-x)&=f\left(t(-x))\right\\&=f\left(t(x))\right\\&=fo\ t\ (x)\end{aligned}

From the above calculation it is concluded that,


\boxed{fo\ t\ (-x)=fo\ t\ (x)}

This implies that the composite function
fo\ t\ (x) is an even function.

If both the function
f(x) and
t(x) are odd function.


\begin{aligned}fo\ t\ (-x)&=f\left(t(-x))\right\\&=f\left(-t(x))\right\\&=-fo\ t\ (x)\end{aligned}

From the above calculation it is concluded that,


\boxed{fo\ t\ (-x)=-fo\ t\ (x)}

This implies that the composite function
fo\ t\ (x) is an odd function.

If the function
f(x) is even and
t(x) is odd.


\begin{aligned}fo\ t\ (-x)&=f\left(t(-x))\right\\&=f\left(-t(x))\right\\&=fo\ t\ (x)\end{aligned}

From the above calculation it is concluded that,


\boxed{fo\ t\ (-x)=fo\ t\ (x)}

This implies that the composite function
fo\ t\ (x) is an even function.

User ArmeniaH
by
6.6k points